Potensi Antibakteria Tanaman Bidara Laut (Ximenia americana) Terhadap Bakteri Vibrio alginolyticus dan V. parahaemolyticus - Ramses Ramses; Fenny Agustina; R. Pramuanggit Panggih Nugroho (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Vibriosis is currently still a major problem in marine aquaculture and is highly dependent on availability of antibacterial agents in its handling. Investigation of antibacterial potential of the coastal plants of Bidara Laut (Ximenia americana) has been carried out. Methods: Parts of the X. americana plant taken are Old Fruit, Young Fruit, Old Leaf, and Young Leaf. A total of ± 200 grams of each part of X. americana plant was taken to be extracted using maceration method. The antibacterial activity test was performed using the Kirby-Bauer disc diffusion method on Muller Hinton Agar (MHA) media. Observations were made in time units, namely every 6 hours of incubation for 24 hours. Results: The tested extract of plant parts of X. americana showed an inhibition zone against the growth of V. alginolyticus and V. parahaemolyticus bacteria in each replication in all-time units of observation. Of the four types of extracts tested, old leaves showed strong category resistance to V. alginolyticus with the highest clear zone diameter of 16 mm (average 14.67 mm) at 6 hours incubation. Young leaves gave the highest of 18 mm (average 16.33 mm) against V. parahaemolyticus at 6 hours incubation. Conclusions: X. americana plants have potential for antibacterial against Vibriosis disease in aquaculture. The ability of power to be seen tended to decrease for all tests until the end of observation, but until the end of observation, the ability of extract inhibition of all parts of the plant was still in the moderate to strong category.